Study on the Influence of Laminated Coupling Structure-fit Parameters on Fatigue Life and Optimization - Huang Yong; Zhou Bowei; Wang Yingchun (Jixie chuandong)
Increasing the fatigue life of the laminated coupling helps to enhance the working stability of the transmission system. To this end, this study establishes a quasi-static mechanical analysis model of the laminated coupling under the action of external torque, and grasps the stress change law of the dangerous part of the lamination. The fatigue life of the laminated sheet is obtained using the S-N curve method. Response surface models of spacer thickness, inclination angle and excess with respect to fatigue life of the laminations are developed by the Box Behnken method. Finally, a study on the optimization of the structure-process parameters of the coupling is carried out. The results show that when the intermediate shaft thickness is 14 mm, the inclination angle is 85.75°, the excess amount is 0.126 mm, and the fatigue life of the coupling is increased by 15.0% compared with the original structure, which ensures the stability and reliability of the shaft system.